Palm Oil and the Dynamics of Community Changes: Lesson Learned From Aceh and West Kalimantan - Subhani; Nazaruddin; Ratri Candrasari; Awaludin Arifin; Ade Ikhsan Kamil (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This paper argue that many experiences have occurred as a result of the introduction of oil palm as a global phenomenon in the context of fulfilling vegetable oil resources as an alternative energy for the future. By using ethnographic methods both in the process of data collection, data analysis and data representation, the authors want to show that community changes are very dynamic in relation to their response to the presence of oil palm as a cash crop. The results of the study show that there are different categories of changes that have occurred in West Kalimantan and Aceh related to the expansion of oil palms. In West Kalimantan, with the strong customary law which is an everyday value, the process of change can still be traced in detail starting from changes in settlement patterns, changes in modes of production and the dynamics that occur from the process of changing modes of production from fields, rubber and oil palm. Meanwhile in Aceh, the process of massive palm oil expansion has raised issues related to labor relations in the industrial context.